2020
DOI: 10.3389/fmech.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Contact Geometry Adaptation in Fretting Wear: A Constructive Review

Abstract: Fretting is a special type of wear, which appears at the contact interface between two solids subjected to constant normal load and periodic tangential forces. Although most studies on fretting have been executed experimentally, some approaches for simulating fretting wear have also been introduced during the last decades. In particular, fretting wear analysis is concerned with the evolution of the surface profiles of the contacting bodies due to wear, and its modeling was executed using numerical, finite-elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…When considering the contact problem with the effect of wear, the issue of contact geometry adaptation [44] should be addressed first. The third body influences the contact pressure distribution not only via the accommodation of the contact displacements, but also via partially filling the variable gap between the surfaces of the first bodies.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the contact problem with the effect of wear, the issue of contact geometry adaptation [44] should be addressed first. The third body influences the contact pressure distribution not only via the accommodation of the contact displacements, but also via partially filling the variable gap between the surfaces of the first bodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is this conforming zone which provides this insensitivity to the elastic stiffness. Besides, Argatov and co-authors revealed analytically, through asymptotic modeling of reciprocating sliding wear, a weak effect of elasticity on surface wear [25][26][27]. Based on this, it seems relevant to apply constant contact stiffness along the simulation which will be more effective especially at large number of cycles where the interface converges to conformal configuration.…”
Section: Identification Of the Winkler Stiffness Parameter From Hertz...mentioning
confidence: 99%
“…, B is the coefficient characterizing the deformation properties of the surface roughness of the elastic halfspace [17,18], E is the elastic modulus of the half-space.…”
Section: (2023) 012001mentioning
confidence: 99%